PERBANDINGAN METODE MAUT DAN OCRA DALAM SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU BERPRESTASI DENGAN PEMBOBOTAN ROC (SDN 101883 PASAR XIII) - Sitanggang, Taufan; Nadeak, Berto; Fadlina, Fadlina (Dharmas Education Journal (DE_Journal), 2024)
The issue encountered in determining outstanding teachers often arises from the ineffectiveness of the results obtained, as well as errors in the scoring of teachers and potential manipulation of scores due to bribery from candidates. To address this problem, solutions involve using the MAUT and OCRA methods with ROC weighting in a Decision Support System. By ranking from the highest to the lowest values, it was found that the MAUT method (0.00610) yields a higher score compared to the OCRA method (0.00243). In this context, a lower value generally indicates a more optimal or better result according to the criteria used. Overall, the OCRA method shows a lower value compared to MAUT, suggesting that OCRA may provide a more optimal solution in the measured context. However, selecting the best method should also consider specific contexts and relevant evaluation criteria.